2008
DOI: 10.2320/matertrans.mer2007278
|View full text |Cite
|
Sign up to set email alerts
|

Aging Behaviors in AZ91D/Al<SUB>18</SUB>B<SUB>4</SUB>O<SUB>33w</SUB> Composite Fabricated by Squeeze Casting

Abstract: Aluminum borate whisker (Al 18 B 4 O 33w , denoted by ABO w ) reinforced AZ91D (Mg-9.1 mass%Al-0.7 mass%Zn) magnesium alloy composite was fabricated by squeeze casting. AZ91D/ABO w composite and AZ91D alloy were aged at 443 K in oil-bath. The composite exhibited an accelerated age-hardening response comparing with AZ91D alloy. Age-hardening efficiency of composite was better than that of AZ91D alloy. It was attributed to the interfacial reaction between AZ91D alloy matrix and ABO w . The interfacial reaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The pressure not only refines the structure but it also offers a favorable effect on the T6 heat treatment response of the alloy, observed in Al-11%Si T6 alloy prepared at 120 MPa [26]. The discontinuities were reduced and the interfacial reactions were observed to be faster in AZ91D/Al 18 B 4 O 33 w metal matrix composites fabricated at high pressures [27]. At high pressure (320 MPa), it was observed that the mechanical properties improve significantly however, the pressure does not affect the type of phases formed during heat treatment.…”
Section: Introductionmentioning
confidence: 98%
“…The pressure not only refines the structure but it also offers a favorable effect on the T6 heat treatment response of the alloy, observed in Al-11%Si T6 alloy prepared at 120 MPa [26]. The discontinuities were reduced and the interfacial reactions were observed to be faster in AZ91D/Al 18 B 4 O 33 w metal matrix composites fabricated at high pressures [27]. At high pressure (320 MPa), it was observed that the mechanical properties improve significantly however, the pressure does not affect the type of phases formed during heat treatment.…”
Section: Introductionmentioning
confidence: 98%